(untitled) (Communications in Computational Physics, 2018)
Lattice Boltzmann model (LBM) in conjunction with an accurate Large Eddy Simulation (LES) technology was proposed to simulate various vortical structures and their evolutions in open pump intakes. The strain rate tensor in the LES model is locally calculated by means of non-equilibrium moments based on Chapman-Enskog expansion, and bounce-back scheme was used for non-slip condition on solid walls and reflection scheme for free surface. The presented model was applied to investigate free-surface and wall-attached vortices for different water levels and flow rate. The vortex position, shapes and vorticities were predicted successfully under three flowing cases (i.e. critical water level (CWL), lower water level, lower flow rate), and the numerical velocity and streamline distribution were analyzed systematically. For CWL based on Froude number considering open channel flows, the shape and the location of various dynamic vortices were captured. Compare to the experimental results of CWL, more vortices were predicted for lower water level, and less vortices were observed for lower flow rate. The predicted velocities and vortex locations are in good agreement with the experimental of a small physical model. The comparisons demonstrated the feasibility and stability of above-mentioned model and numerical method in predicting vortex flows inside open pump intakes.